Streptomyces tagetis sp. nov., a chromomycin producing bacteria isolated from the roots of Tagetes patula - Chhetri, Geeta; Kim, Myeong Ji; Kim, Inhyup; Tran, Duc V. H.; Kim, Young-Woo; Kim, Hyun Woo; Seo, Taegun (Frontiers in Microbiology, 2024)
A novel halotolerant actinobacterium, designated RG38 T , capable of producing black extracellular melanin pigment on SP2 agar, was isolated from the roots of Tagetes patula. Comparative analysis of the 16S rRNA gene sequence revealed the highest similarity to Streptomyces collinus NBRC 12759 T (99.3%). Phylogenetic analysis showed that strain RG38 T clustered within the genus Streptomyces forming a monophyletic cluster with its close relatives. The average nucleotide identity (ANI), digital DNA-DNA hybridization (dDDH) and amino-acid identity (AAI) values between strain RG38 T and related species within the genus Streptomyces were well below the standard threshold for prokaryotic species delineation. The DNA G+C content of strain RG38 T was determined to be 73.3%. The genome size measured 7,150,598 bp comprising 17 contigs and encompassed 6,053 protein coding genes.AntiSMASH analysis of the whole genome revealed 35 putative biosynthetic gene clusters (BGCs) responsible for various secondary metabolites. Among these clusters, two gene clusters exhibited 100% similarity to the chromomycin A3, albaflavenone and anthracimycin, respectively. These compounds been reported to possess significant anticancer and antibacterial activities. LC-MS based analysis and coupled with further isolation studies confirmed the production of chromomycins A2 (1), A3 (2), and their derivatives, along with their antibiotic activities. These findings underscore the potential of this novel strain as a novel resource for the discovery of diverse antimicrobial compounds. This study is the first to report an antimicrobial compound producing Streptomyces species isolated from medicinal plant T. patula. Based on a polyphasic study, strain RG38 T isolated from an unexplored habitat with a high potential for new natural products, represents a novel species in within the genus Streptomyces.Accordingly, we propose the name Streptomyces tagetis sp. nov. for this novel species, with the type strain is RG38 T (=KCTC 49624 T =TBRC 15113 T ).